Systemic Financial Crises, Balance Sheets, and Model Uncertainity - Weeks, Melvyn (IMF Working Papers; Working Paper ;, 2001)
This paper empirically examines the probability and intensity of financial crises during the 1990s with a view to informing crisis prevention and mitigation policies. The econometric analysis uses a decision-theoretic approach, rather than the more standard general-to-specific approach, to address the high degree of model uncertainty. The results affirm the importance of balance sheets in the probability and intensity of financial crises, especially corporate balance sheet stresses and foreign exchange liquidity shortfalls. Model uncertainty is a bigger problem for estimating crisis intensity compared to crisis probability.